2022
DOI: 10.1371/journal.pone.0271306
|View full text |Cite
|
Sign up to set email alerts
|

The mental health benefits of visiting canals and rivers: An ecological momentary assessment study

Abstract: Existing evidence shows positive effects of being in nature on wellbeing, but we know little about the mental health benefits of spending time near canals and rivers specifically. This study investigates the association between visits to canals and rivers and mental wellbeing. We addressed the following questions: Are visits to canals and rivers associated with higher levels of mental wellbeing? Does this association depend on age and gender? Does this association vary between people with and without a diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…www.nature.com/scientificreports/ Consistent with our second hypothesis, we found that the beneficial effect on mental wellbeing is still significant after the encounter with birds has taken place. This is consistent with our earlier research on the benefits of green 10 and blue 18 spaces which demonstrated time-lasting benefits for mental health. Perhaps unsurprisingly, the beneficial effect of seeing or hearing birds on mental wellbeing does wane over time.…”
Section: Discussionsupporting
confidence: 92%
“…www.nature.com/scientificreports/ Consistent with our second hypothesis, we found that the beneficial effect on mental wellbeing is still significant after the encounter with birds has taken place. This is consistent with our earlier research on the benefits of green 10 and blue 18 spaces which demonstrated time-lasting benefits for mental health. Perhaps unsurprisingly, the beneficial effect of seeing or hearing birds on mental wellbeing does wane over time.…”
Section: Discussionsupporting
confidence: 92%
“…Such positive effects have also been corroborated by Wood et al [45] and Bergou et al [46]. Wood et al [45] suggest that ecological diversity in urban green spaces (such as tree-planting and various wildlife emergence) will result in psychological restoration amongst participants from multiple ethnic groups, while Bergou et al [46] highlight that urban dwellers' visits to green and blue spaces will result in a greater level of mental wellbeing.…”
Section: Environment and Biodiversity Loss Belief Formulationmentioning
confidence: 86%
“…Urban canal, by Slbs (CC BY-SA 2.0); https://commons.wikimedia.org While people living in busy cities may find it hard to go to the beaches or beautiful streams and lakes in the countryside, it is more plausible to visit the local water bodies. In fact, just walking along the urban canals or rivers can also improve one's mood and well-being [3]. It may even make one feels safer and more socially included.…”
Section: Water That Soothes the Mindmentioning
confidence: 99%